Exploring digital promotion as a tool for community empowerment: A participatory analysis of website utilization in Sumber Urip tourism village - R. Muhammad Ihsan; Elyusra Elyusra (Priviet Social Sciences Journal, 2025)
This study explores digital promotion as a tool for community empowerment through the use of the website desasumberurip.com in Sumber Urip Tourism Villages. As digital transformation has become increasingly crucial for rural tourism development, village management has adopted a website to enhance promotion and support local economic activities. Employing a descriptive qualitative approach, the study involved in-depth interviews, focus group discussions, observations, and content analysis of the website. Participants included key village stakeholders such as management, tourism unit leaders, and digital administrators. The findings reveal that the website serves as an initial step in digitalizing tourism promotion, offering accessible information about tourism attractions, cultural events, and local products. However, its current structure remains static, which limits its interactivity and timely updates. The identified challenges include limited digital literacy among the broader community, inadequate technological infrastructure, and the absence of integrated e-commerce features for local MSMEs. Despite these limitations, the website has begun to engage young community members in content management, indicating emerging opportunities for digital community empowerment. The study concludes that while the website represents significant progress in promoting Sumber Urip Tourism Villages, further development is required. Future efforts should focus on transitioning to a dynamic web platform, enhancing storytelling-based content, and increasing community participation to maximize the impact of digital promotions. Ultimately, optimizing the website holds potential not only for boosting tourism visibility, but also for empowering local communities and strengthening the village’s digital identity.